Identifikasi Tercampurnya Minyak Lumas dengan Air pada Carter Cargo Oil Pump Turbine di MT. Nectar - Krisna Handika Wicaksono; Amad Narto; Kresno Yuntoro (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This study examines a crucial problem that occurred on board the MT. Nectar, namely air contamination in the lubricating oil of the Cargo Oil Pump Turbine COPT, which is a critical system in supporting the download and unloading process of crude oil. This contamination resulted in a significant decrease in pump performance, increasing the risk of malfunction that impacts equipment safety and the operational efficiency of the ship. This problem not only has a technical impact, but also requires proper maintenance management handling. Using a qualitative approach through direct observation, interviews with crew members, and documentation studies of the maintenance and operation history of the lubrication system, this study analyzed the root cause using the SHEL (Software, Hardware, Environment, Liveware) model and Fishbone Diagram. The analysis results indicate that the main causes of contamination are leaks in the labyrinth seal, inadequate condenser vacuum, and wear on metal bearings due to suboptimal lubrication. To address this problem, the study recommends improving compliance with Plan Maintenance System PMS procedures, implementing routine and periodic inspections of the entire lubrication system, using high-quality components, and improving technical training for crew members to strengthen their understanding of the lubrication system. In addition, a digital monitoring system is needed for early detection of contaminants in the oil. These steps aim to maintain the darkness and efficiency of the COPT system to ensure optimal ship operations. This research is expected to be a useful reference for ship crews, shipping companies, and cadets at the Semarang Maritime Polytechnic PIP in understanding the importance of lubrication systems and preventing contamination in auxiliary machinery on ships. This research is expected to be a useful reference for ship crews, shipping companies, and cadets at the Semarang Maritime Polytechnic PIP in understanding the importance of lubrication systems.